Immunogenetic markers associated with a naturally acquired humoral immune response against an N-terminal antigen of Plasmodium vivax merozoite surface protein 1 (PvMSP-1). (December 2016) - Cassiano, Gustavo; Furini, Adriana; Capobianco, Marcela; Storti-Melo, Luciane; Almeida, Maria; Barbosa, Danielle; Póvoa, Marinete; Nogueira, Paulo; Machado, Ricardo
Abstract Background Humoral immune responses against proteins of asexual blood-stage malaria parasites have been associated with clinical immunity. However, variations in the antibody-driven responses may be associated with a genetic component of the human host. The objective of the present study was to evaluate the influence of co-stimulatory molecule gene polymorphisms of the immune system on the magnitude of the humoral immune response against aPlasmodium vivax vaccine candidate antigen. Methods Polymorphisms in theCD28, CTLA4, ICOS, CD40, CD86 andBLYS genes of 178 subjects infected withP. vivax in an endemic area of the Brazilian Amazon were genotyped by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The levels of IgM, total IgG and IgG subclasses specific for ICB2-5, i.e., the N-terminal portion ofP. vivax merozoite surface protein 1 (PvMSP-1), were determined by enzyme-linked immuno assay. The associations between the polymorphisms and the antibody response were assessed by means of logistic regression models. Results After correcting for multiple testing, the IgG1 levels were significantly higher in individuals recessive for the single nucleotide polymorphism rs3116496 inCD28 (p = 0.00004). Furthermore, the interaction betweenCD28 rs35593994 andBLYS rs9514828 had an influence on the IgM levels (p = 0.0009). Conclusions The results of the present study support the hypothesis that polymorphisms in the genes of co-stimulatory components of the immune system can contribute to a natural antibody-driven response againstP. vivax antigens.